PELATIHAN DAN SOSIALISASI KONSERVASI ENERGI LISTRIK PLTS TERPUSAT DAN BEBAN RUMAH TANGGA PADA MASYARAKAT KAMPUNG DOMANDE KECAMATAN MALIND - Frederik Haryanto Sumbung; Yohanes Letsoin (Musamus University, 2020)
Electricity is an indicator of progress in the social life of people in an area, including the people of Domande village. The existence of training activities and socialization of Electric Energy Conservation in stand alone Photo Voltaic (PV) power system and Household Burden on the Village Community in Domande Village, Malind District, although in terms of the number involved as limited participants, the participants who attended this activity were very enthusiastic. This is evidenced by the active participation of the participants in carrying out practical activities in experiment 1 to experiment 3 which can be completed well, although with a very limited time. Domande village is one of the villages that is far from the power plant managed by PT PLN, so that through the government program in 2013 a stand alone Photo Voltaic (PV) power system was built. However, in its operation, the stand alone Photo Voltaic (PV) power system cannot operate optimally, so currently it only operates during the day. With this condition, it is necessary to have skills in customers, in this case the people of Domande village, to take advantage of the Photo Voltaic (PV) power system operation so that it can be used at night, namely by taking the initiative to have equipment and materials that can store energy for use at night. For this, it is necessary to have relevant knowledge and skills, especially basic knowledge and skills in the field of electricity and renewable energy. The existence of this activity is fundamentally able to help the community, especially those involved as participants in gaining basic knowledge and skills on electrical installations and renewable energy, which is the implementation of the energy conservation program. It is hoped that in its application the participants can duplicate the basic knowledge and skills that have been obtained from other communities around Domande Village in particular, and can consult with higher education institutions if there are problems and obstacles in their application